Programa economico y social de Mexico (una controversia) =Social and economic program of Mexico (a controversy) - Cumberland, W.W.; McGowan, R.A.; Thorning, Joseph; Beteta, Ramon (Ciudad de Mexico: [s.n.], 1935)
"Neerslag van een tegensprekelijk debat"